Projected Population Benefit of Increased Effectiveness and Coverage of Influenza Vaccination on Influenza Burden — United States - Hughes, Michelle M. (Clin Infect Dis, 2020)
BACKGROUND: Vaccination is the best way to prevent influenza; however, greater benefit could be achieved. To help guide research and policy agendas, we aimed to quantify the magnitude of influenza disease that would be prevented through targeted increases in vaccine effectiveness (VE) or coverage. METHODS: For three influenza seasons (2011–12, 2015–16, and 2017–18) we used a mathematical model to estimate the number of prevented influenza-associated illnesses, medically-attended illnesses, and hospitalizations across five age groups. Compared with estimates of prevented illness during each season, given observed VE and coverage, we explored the number of additional outcomes that would be prevented from a 5% absolute increase in VE or coverage or achieving 60% VE or 70% coverage. RESULTS: During the 2017–18 season, compared with the burden already prevented by influenza vaccination, a 5% absolute VE increase would prevent an additional 1,050,000 illnesses and 25,000 hospitalizations (76% among those aged ≥65 years) while achieving 60% VE would prevent an additional 190,000 hospitalizations. A 5% coverage increase would result in 785,000 fewer illnesses (56% among those aged 18–64 years) and 11,000 fewer hospitalizations; reaching 70% would prevent an additional 39,000 hospitalizations. CONCLUSIONS: Small, attainable improvements in effectiveness or coverage of influenza vaccine could lead to substantial additional reductions in influenza burden in the U.S. Improvements in VE would have the greatest impact in reducing hospitalizations in adults aged ≥65 years and coverage improvements would have the largest benefit in reducing illnesses in adults aged 18–49 years.